The Unified Protocol for Transdiagnostic Treatment of Emotional Disorders: Preliminary Exploration of Effectiveness for Group Delivery. (March 2015) - Bullis, Jacqueline R.; Sauer-Zavala, Shannon; Bentley, Kate H.; Thompson-Hollands, Johanna; Carl, Jenna R.; Barlow, David H.
The Unified Protocol for Transdiagnostic Treatment of Emotional Disorders (UP) has demonstrated promising results among patients with heterogeneous anxiety and comorbid depressive disorders when delivered on an individual basis, but greater efficiencies may be achieved with group-based applications. The aim of the present study was to provide a preliminary exploration of the UP when delivered in a group format. Among diagnostically diverse patients ( N = 11), the UP group treatment resulted in moderate to strong effects on anxiety and depressive symptoms, functional impairment, quality of life, and emotion regulation skills, as well as good acceptability and overall satisfaction ratings from patients. Three clinical cases are presented in detail to illustrate the group-based UP delivery, followed by a critical discussion of associated challenges and proposed guidelines for group administration, as well as directions for future research.